From the power to discriminate to the power to protect. The word race between Fascist legislation and the Italian Constitution - Orrù, Alice (Rivista Italiana di Filosofia del Linguaggio, 2023)
Despite its high frequency in basic Italian vocabulary, the word race, of equine origin and later acquiring typological and biological human meaning, historically conceals a semantic tangle. Its presence in the Italian Constitution was strongly desired by the Constituent Assembly and motivated by the heavy historical, (para)scientific, political, and juridical legacy of colonial and anti-Jewish laws. However, it continues to raise issues that unfold on multiple binomial planes: common and technical language, totalitarian and democratic legislation, exclusive and inclusive power, and deprivation and protection of rights, further implying the relationship between individual and community. Not just in Italy, linguistic and political values embodied by race interdisciplinarily develop from the question of possible synonymy with supposed closely related words. Nevertheless, all four alternative proposals (maintaining, eliminating, replacing, combining) still prove to be a harbinger of further problems, discouraging from siding with one another. This semantic labyrinth is not exempt from revealing the inescapability of race from its intrinsic remembrance value. In this sense, the word pragmatically becomes a consistent deterrent to the denial of civil and political rights now guaranteed by substantive and no longer formal equality.